2004
DOI: 10.1016/j.clpt.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A variant 2677A allele of the gene affects fexofenadine disposition

Abstract: The plasma concentrations of fexofenadine after a single oral administration were lower in 2677AA/3435CC subjects than in subjects with the other 5 genotype combinations of the SNPs of G2677T/A and C3435T. These findings confirm the importance of analyzing MDR1 haplotypes and provide a plausible explanation for the conflicting results regarding the effect of MDR1 polymorphisms on the disposition of P-gp substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
46
3
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 38 publications
9
46
3
5
Order By: Relevance
“…Similarly, in Brazilian hypercholesterolemic subjects, the frequency was 0.47 for T allele (Rodrigues et al, 2005). In addition, the frequency found in our study, for the T allele of the variant 3435C> T is similar to that observed in Asian population such as Koreans (0.37) (Yi et al, 2004), higher in Rapanui populations (0.75) (Wielandt et al), and differs significantly from that observed in Afro-Americans (0.21) (Kajinami et al, 2004b), Africans (0.17), European Caucasian (0.52) (Ameyaw et al, 2001) and Oceania population (0.53) (Roberts et al, 2002).…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, in Brazilian hypercholesterolemic subjects, the frequency was 0.47 for T allele (Rodrigues et al, 2005). In addition, the frequency found in our study, for the T allele of the variant 3435C> T is similar to that observed in Asian population such as Koreans (0.37) (Yi et al, 2004), higher in Rapanui populations (0.75) (Wielandt et al), and differs significantly from that observed in Afro-Americans (0.21) (Kajinami et al, 2004b), Africans (0.17), European Caucasian (0.52) (Ameyaw et al, 2001) and Oceania population (0.53) (Roberts et al, 2002).…”
Section: Discussionsupporting
confidence: 72%
“…Most common approach in determination of the influence of gene variation is haplotype assessment because it may provide a better understanding of the observed inconsistences and are promising predictor of the functional consequences of ABCB1 polymorphisms. It has been confirmed that the use of ABCB1 haplotypes is superior in prediction of the pharmacokinetics of digoxin [22], cyclosporine [23] and fexofenadine [24], as well as intestinal expression of ABCB1 mRNA [25]. A correlation was observed between the 1236T, 2677T and 3435T haplotype and decreased irinotecan clearance in Japanese patients with cancer.…”
mentioning
confidence: 55%
“…Drug metabolizing enzymes and membrane transporters of these agents affect their in vivo disposition, and polymorphisms of these genes may influence function and explain some of the inter-individual variability. [1][2][3][4][5][6][7] Commonly used cytotoxics such as docetaxel and doxorubicin have narrow therapeutic indices and significant inter-individual variations in drug disposition. Both drugs are effluxed from cells expressing ABCB1 and metabolized mainly in the liver, with CYP3A being the main metabolizing enzyme of docetaxel.…”
Section: Introductionmentioning
confidence: 99%